ATTITUDE, SUBJECTIVE NORM, PERCEIVED BEHAVIORAL CONTROL, AND INFORMATION CASCADE EFFECTS ON INVESTMENT INTENTION: FINANCIAL LITERACY AS ANTECEDENT TO ATTITUDE - Natalia, Elisse; Sihombing, Sabrina Oktaria (DeReMa (Development Research of Management): Jurnal Manajemen, 2025)
The development of financial technology has brought significant transformation to the global financial sector, including in Indonesia. In Indonesia, the P2PL industry has shown rapid growth. This study aims to examine the influence of investment attitude, subjective norm, perceived behavioral control, and information cascade on the intention to invest in P2PL, with financial literacy as an antecedent of attitude. Although numerous studies have explored the factors influencing investment intention, the variable of information cascade remains under-researched, particularly in the context of P2PL. This is a quantitative study employing a causal research design. The object of the study is peer-to-peer lending (P2PL). Data were collected through a questionnaire consisting of 28 indicators measured on a 5-point Likert scale. The sampling design used is purposive sampling, targeting individuals who have previously invested in P2PL platforms within last three months. The study involved 40 participants in the preliminary study and 280 in the main study. The analysis method used is Partial Least Squares Structural Equation Modeling (PLS-SEM). The preliminary study resulted in the removal of 8 indicators, which were excluded from the actual study. The findings from the actual study show that attitude toward investing, subjective norm, and perceived behavioral control have a positive and significant effect on investment intention, while information cascade does not have a significant effect. Additionally, investment attitude mediates the influence of financial literacy on investment intention. The Importance-Performance Map Analysis (IPMA) results indicate that subjective norm and perceived behavioral control should be prioritized in strategy improvement. Abstrak dalam Bahasa Indonesia  Perkembangan teknologi keuangan telah membawa transformasi yang signifikan pada sektor keuangan global, termasuk di Indonesia. Di Indonesia, industri peer-to-peer lending (P2PL) menunjukkan pertumbuhan yang pesat. Penelitian ini bertujuan untuk mengkaji pengaruh sikap terhadap investasi, norma subjektif, persepsi kontrol perilaku, dan information cascade terhadap niat berinvestasi pada P2PL, dengan literasi keuangan sebagai anteseden sikap. Meskipun banyak penelitian telah mengeksplorasi faktor-faktor yang memengaruhi niat berinvestasi, variabel information cascade masih jarang diteliti, khususnya dalam konteks P2PL. Penelitian ini merupakan penelitian kuantitatif dengan desain riset kausal. Objek penelitian adalah peer-to-peer lending (P2PL). Data dikumpulkan melalui kuesioner yang terdiri dari 28 indikator yang diukur menggunakan skala Likert 5 poin. Desain pengambilan sampel yang digunakan adalah purposive sampling, dengan sasaran individu yang telah berinvestasi pada platform P2PL dalam tiga bulan terakhir. Penelitian ini melibatkan 40 responden pada studi pendahuluan dan 280 responden pada studi utama. Metode analisis yang digunakan adalah Partial Least Squares Structural Equation Modeling (PLS-SEM). Studi pendahuluan menghasilkan penghapusan 8 indikator yang tidak digunakan pada studi utama. Hasil penelitian utama menunjukkan bahwa sikap terhadap investasi, norma subjektif, dan persepsi kontrol perilaku berpengaruh positif dan signifikan terhadap niat berinvestasi, sedangkan information cascade tidak berpengaruh signifikan. Selain itu, sikap terhadap investasi memediasi pengaruh literasi keuangan terhadap niat berinvestasi. Hasil Importance-Performance Map Analysis (IPMA) menunjukkan bahwa norma subjektif dan persepsi kontrol perilaku perlu diprioritaskan dalam perbaikan strategi.